Decision Support System for Mining Land Clearing in Magelang Regency Using the Simple Attribute Rating Technique (SMART) Method - Gregorius Hugo Himawan (Institute of Computer Science (IOCS), 2021)
Magelang Regency is a district located on the slopes of Mount Merapi in the western region, this existence makes Magelang Regency has potential in the field of mineral mining in the form of sand and rock. The number of riots that occurred because of the opening of the mine that was not in accordance with the provisions of the Energy, Resources and Minerals Service made the candidates for the mine opener confused in determining the place that was in accordance with the provisions of the service. Each prospective mine opener has his own considerations in determining the location. This final project is made to help provide recommendations to prospective mine openers in determining the location to be opened by considering the distance from settlements, distance from the highway, area, type of mine, and mine location. Decision Support System was built using PHP and MySQL. User can select criteria to compare each location. The method used to provide recommendations is the Simple Multi Attribute Rating Technique (SMART) based on the criteria selected by the user. The final result obtained is the recommended mine location based on the order of the final scores of the compared mine sites.